Preparation, modification, and clinical application of porous tantalum scaffolds - Wang, Xinyi; Zhou, Ke; Li, Yada; Xie, Hui; Wang, Benjie (Frontiers in Bioengineering and Biotechnology, 2023)
Porous tantalum (Ta) implants have been developed and clinically applied as high-quality implant biomaterials in the orthopedics field because of their high corrosion resistance, biocompatibility, osteointegration, and bone conductivity. Porous Ta allows fine bone ingrowth and new bone formation through the inner space because of its high porosity and interconnected pore structure. It contributes to rapid bone integration and long-term stability of osseointegrated implants. Porous Ta has excellent wetting properties and high surface energy, which facilitate the adhesion, proliferation, and mineralization of osteoblasts. Moreover, porous Ta is superior to classical metallic materials in avoiding the stress shielding effect, minimizing the loss of marginal bone, and improving primary stability because of its low elastic modulus and high friction coefficient. Accordingly, the excellent biological and mechanical properties of porous Ta are primarily responsible for its rising clinical translation trend. Over the past two decades, advanced fabrication strategies such as emerging manufacturing technologies, surface modification techniques, and patient-oriented designs have remarkably influenced the microstructural characteristic, bioactive performance, and clinical indications of porous Ta scaffolds. This study offers an overview of the fabrication methods, modification techniques, and orthopedic applications of porous Ta implants.